Development of dam controller technology water level and alert system using Arduino UNO - Mazratul Firdaus Mohd Zin; Farid Zuhri Kamal; Syila Izawana Ismail; Ku Siti Syahidah Ku Mohd Noh; Abdul Hafiz Kassim (Institute of Advanced Engineering and Science, 2023)
Recently, various water level detection monitoring systems integrations were implemented to various places such as rivers and reservoirs to avoid floods. Thus, it is determined to construct a project primarily focused on water level management, named dam controller technology (DCOTech). DCOTech is a system that controls the amount of water in a reservoir using a microcontroller ATMEGA328p and several functions to prevent flash floods. Water sustainability requires proper monitoring via sensors and a controller. Moreover, a buzzer is used in DCOTech to give a warning signal to the people around and the residents. The water level sensor was constructed with a metal plate attached at both the bottom and top edges of the reservoir. The results obtained met expectations; whenever the sensor detects the water level is low, the green light emitting diode (LED) is turned on; otherwise, when the sensor detects the water level is high, the drain valve is opened, and simultaneously, turned on the buzzer to alert the surrounding. The goal of this project is to integrate a control system into an autonomous water level controller. This study aims to provide a solution to unexpected floods and to notify inhabitants when the water level is dangerously high.